If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2 = 2x + 3 Reorder the terms: -2 + 5x = 2x + 3 Reorder the terms: -2 + 5x = 3 + 2x Solving -2 + 5x = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 5x + -2x = 3 + 2x + -2x Combine like terms: 5x + -2x = 3x -2 + 3x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + 3x = 3 + 0 -2 + 3x = 3 Add '2' to each side of the equation. -2 + 2 + 3x = 3 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 3 + 2 3x = 3 + 2 Combine like terms: 3 + 2 = 5 3x = 5 Divide each side by '3'. x = 1.666666667 Simplifying x = 1.666666667
| 5x+4-2x=22 | | x-10x=25 | | .33(3*3+192)=x | | 2k(k+11)=11 | | 8x+24=2 | | 5(6-3)-4=x | | 5(3*27-7*3)=x | | 2x^2-1=3x | | -4+2[5k-6]=-3k-39 | | x+18x+41=7 | | 4+5x+x=-14 | | 2+5=5-9 | | 4(2)=8(m-8) | | 75=3[-6n-5] | | (7x+9)(x-8)=0 | | 5x+4y=53 | | 24=6[-x-3] | | 6a+4=-2 | | 5b(4b^3-6b^2-6)= | | 2a+30=5a | | x-10x+5=18 | | -4x+21=3x+91 | | (5x+2)(x-8)=0 | | -15=x-6x+10 | | .50(2x-6)-4x=6x-(4x-7) | | =x^2-7x+6 | | 6=-3[x+2] | | 5x^2-38x-16=y | | =x^2+4x-5 | | y=(5x+2)(x-8) | | -19+17x=16x-9 | | 9x+16=43 |